(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2002)
Porphyrias are disorders characterized by identical neurological disfunctions arising from an enzymatic defect in the heme biosynthetic pathway. The acute porphyrias, namely 5-aminolevulinic acid dehydratase porphyria, acute intermittent porphyria, hereditary coproporphyria and variegate porphyria are caused respectively by deficiencies in the enzymes 5aminolevulinic acid dehydratase, porphobilinogen deaminase, coproporphyrinogen decarboxilase and protoporphyrinogen oxidase. Acute porphyrias are characterized by an increase of plasma and liquor 5aminolevulinic acid levels, followed by increased urinary excretion of this compound. Increases in the urinary excretion of porphyrins or other porphyrin precursors may be observed depending on the type of acute porphyria. Diagnosis of acute porphyria cases rests on the measurement of porphyrins or porphyrin precursors in urine, blood and faeces. Since the clinical manifestations are generally triggered by ambiental or acquired factors, screenings for gene carriers among relatives of AIP are important to identify latent cases. The diagnosis of gene carriers was usually based on the determination of the activity of blood heme biosynthetic enzymes and more recently on DNA analysis.